Copper-manganese spinel nano material with high oxygen vacancy content as well as preparation and application of copper-manganese spinel nano material

By reacting the abandoned activated carbon and metal salt in an alkaline solution, the copper -manganese spinel -nano -nano -material material with high oxygen vacuum content is prepared to solve the problem of high waste activated carbon treatment costs, and achieve efficient VOCS catalytic oxidation degradation and resourceization of resourceization. use.

CN119346133APending Publication Date: 2025-01-24NANJING INST OF ENVIRONMENTAL SCI MINIST OF ECOLOGY & ENVIRONMENT OF THE PEOPLES REPUBLIC OF CHINA
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411641023.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The lack of efficient resource utilization technology for waste activated carbon in the prior art, resulting in high processing costs and unenvironmental protection.

Method used

By reacting the abandoned activated carbon as an additive and metal salt in an alkaline solution, the copper -manganese spinel nano -nano -material material with high oxygen vacuum content is prepared to catalyze the oxidation degradation of volatile organic matter.

Benefits of technology

The resource utilization of abandoned activated carbon has been realized. The prepared catalysts have an efficient VOCS removal rate in the temperature range of 180 to 300 ° C, and the process is simple and low in cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346133A_ABST
    Figure CN119346133A_ABST
Patent Text Reader

Abstract

The invention relates to a copper-manganese spinel nano material with high oxygen vacancy content and preparation and application thereof, and the preparation method comprises the following steps: dissolving copper salt and manganese salt in deionized water, uniformly stirring, then adding waste activated carbon powder, and fully stirring to obtain a uniformly dispersed mixed solution; adding an excessive amount of the alkaline solution into the mixed solution to fully precipitate metal, carrying out suction filtration and washing on the reaction precipitate after the reaction is finished until the suction filtration liquid is neutral, and separating to obtain a precipitate product; the precipitation product is dried and then transferred into a muffle furnace to be calcined, and the copper-manganese spinel type catalytic material with the high oxygen vacancy content is obtained. The obtained catalytic material has high catalytic performance and can be used for efficient catalytic oxidation degradation of VOCs, and meanwhile resource utilization of waste activated carbon is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of transition metal oxide spinel catalysts, in particular to a copper-manganese spinel nano material with a high oxygen vacancy content and preparation and application thereof. Background Art

[0002] Volatile organic compounds (VOCs) are particulate matter and important precursors of ozone destruction and photochemical smog, which have a significant impact on ecosystems and human health. Catalytic oxidation technology is one of the most promising and effective technologies for removing VOCs, and is the most widely used technology in practical applications. The key to catalytic oxidation to remove VOCs is the selection of catalysts, and the research on efficient catalysts has always been a hot topic in catalytic oxidation technology.

[0003] Improper treatment and disposal of hazardous waste will cause damage to the environment and threaten human health. Rational use of hazardous waste and maximizing economic benefits are the best options for hazardous waste treatment and disposal. Waste activated carbon after VOCs adsorption is a hazardous waste, and pyrolysis, incineration or chemical treatment are commonly used treatment methods for harmless treatment. These harmless treatments of waste activated carbon have the disadvantages of high cost or high energy consumption. Therefore, the prior art lacks a technical solution for efficient resource utilization of waste activated carbon. Summary of the invention

[0004] In view of the shortcomings of the prior art, the present invention provides a copper-manganese spinel nanomaterial with a high oxygen vacancy content and its preparation and application, with the purpose of preparing a high-performance catalyst for catalytic oxidation degradation of VOCs and realizing the resource utilization of waste activated carbon.

[0005] The technical solution adopted by the present invention is as follows:

[0006] The present invention provides a method for preparing a copper-manganese spinel nanomaterial with a high oxygen vacancy content, the preparation method comprising the following steps:

[0007] Dissolve the metal salt in deionized water, stir evenly, then add the waste activated carbon powder, stir thoroughly to obtain a uniformly dispersed mixed solution;

[0008] Adding an excess amount of the alkaline solution to the mixed solution to fully precipitate the metal, and after the reaction is completed, filtering and washing the reaction precipitate until the filtrate is neutral, and separating and obtaining a precipitated product;

[0009] The precipitated product is dried and then transferred to a muffle furnace for calcination to obtain a copper-manganese spinel catalytic material with a high oxygen vacancy content;

[0010] The metal salts include copper salts and manganese salts.

[0011] Further technical solutions are:

[0012] The molar ratio of the waste activated carbon to the metal salt is 0.14 to 1;

[0013] The molar ratio of the copper salt to the manganese salt is 1:1.25 to 1:2.5, and the total concentration of the copper salt and the manganese salt in the mixed solution is 2 to 3 mol / L.

[0014] The calcination treatment is performed at 400-600° C. for 2-5 hours.

[0015] The drying process is carried out at 95 to 120° C. for 12 to 24 hours.

[0016] The molar ratio of the alkaline solution to the metal salt is 1:2.4 to 1:3.

[0017] The copper salt includes one or more of copper nitrate, copper sulfate, copper chloride, and organic copper salts; the manganese salt includes one or more of manganese nitrate, manganese sulfate, manganese chloride, and organic manganese salts.

[0018] The alkaline solution is sodium hydroxide, potassium hydroxide, or ammonia solution; the concentration of the alkaline solution is 4-8 mol / L.

[0019] After the metal salt is dissolved in deionized water, the stirring time is 30 to 60 minutes; after the waste activated carbon powder is added, the sufficient stirring time is 60 to 240 minutes; after the excess alkaline solution is added to the mixed solution, the mixture is sufficiently and rapidly stirred for 40 to 80 minutes to fully precipitate the metal.

[0020] The waste activated carbon is waste activated carbon generated in the process of treating industrial waste gas, waste water or indoor polluted gas.

[0021] The present invention also provides an application, in which the copper-manganese spinel-type catalytic material with a high oxygen vacancy content obtained by the preparation method is applied to the catalytic oxidation degradation of VOCs.

[0022] The beneficial effects of the present invention are as follows:

[0023] The present invention uses waste activated carbon as an additive and prepares a VOCs catalyst with a high oxygen vacancy content in a simple strategy, thereby improving the VOCs removal rate of the catalyst in the temperature range of 180 to 300° C. and realizing the resource utilization of solid waste.

[0024] The present invention specifically has the following advantages

[0025] The present invention uses waste activated carbon from hazardous waste after adsorption as an additive, and prepares a transition metal oxide spinel material with abundant oxygen vacancies by taking advantage of the characteristic that carbon consumes oxygen during calcination, wherein the spinel has a special tetrahedral and octahedral structure, and has excellent catalytic activity, good thermal stability and adjustability. The present invention only needs to control the amount of waste activated carbon added without other complicated and tedious treatments, and can regulate the oxygen vacancies of the material, thereby affecting the catalytic performance, and can be used for efficient catalytic oxidation degradation of VOCs, achieving waste treatment with waste.

[0026] The preparation method of the present invention is simple and easy to operate, waste activated carbon is easy to obtain, and the cost is low. It can be applicable to low-cost, large-scale material production and promote the development of clean energy technology.

[0027] Other features and advantages of the present invention will be set forth in the following description or may be learned by practicing the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The XRD diagrams of the catalysts prepared in Examples 1 to 4 of the present invention and Comparative Example 1 are shown.

[0029] Figure 2 This is a diagram showing the catalytic oxidation effect of toluene using the catalysts prepared in Examples 1 to 4 of the present invention and Comparative Example 1.

[0030] Figure 3 It is the N2 adsorption isotherm diagram of the catalysts prepared in Examples 1, 2, 4 of the present invention and Comparative Example 1.

[0031] Figure 4 The EDS element distribution spectra of the catalysts prepared in Example 2 of the present invention and Comparative Example 1 are shown.

[0032] Figure 5 The EPR diagrams of the catalysts prepared in Example 2 of the present invention and Comparative Example 1 are shown. DETAILED DESCRIPTION

[0033] The specific implementation of the present invention is described below with reference to the accompanying drawings.

[0034] Example 1

[0035] The method for preparing a copper-manganese spinel nanomaterial with a high oxygen vacancy content (i.e., a high oxygen defect content) of the present embodiment specifically comprises the following steps:

[0036] S1. Take 0.02 mol Cu(NO3)2·3H2O and 0.04 mol Mn(NO3)2·5H2O in 20 mL of deionized water and stir at 60°C for 30 min; then add 0.1 g of waste activated carbon powder and continue stirring for 2 h to make the carbon material evenly distributed in the solution to obtain a carbon material solution that adsorbs metal ions.

[0037] S2. Add 20 mL of 5 mol / L NaOH solution to the solution obtained in S1 to precipitate all metals in the solution. Filter the obtained precipitate and wash it 4 times until the filtrate is neutral.

[0038] S3. Dry the separated precipitated product in an oven at 95° C. for 12 h, and then transfer it to a muffle furnace at 500° C. and calcine it for 3 h to obtain a copper-manganese spinel catalyst with a high oxygen vacancy content.

[0039] See also Figure 1 When 0.1 g of waste activated carbon was added, CuMn2O4 spinel was successfully synthesized. The N2 adsorption isotherm of the obtained sample is shown in Figure 3 It can be seen that it conforms to the type IV adsorption isotherm and has an obvious H3 hysteresis loop, indicating that the spinel obtained in Example 1 has an irregular mesoporous structure.

[0040] In order to verify the VOCs catalytic oxidation performance of the obtained copper-manganese spinel catalyst with high oxygen vacancy content, a toluene catalytic performance test was performed on it, including the following steps:

[0041] 100 mg of the prepared copper-manganese spinel catalyst with high oxygen vacancy content was loaded into a fixed-bed quartz tube reactor, and a VOCs catalytic oxidation degradation experiment was carried out under air atmosphere, wherein the background concentration of toluene was 300 ppm, the total flow rate was 100 ml / min, and the space velocity was 60000 mL·h -1 ·g -1 , reaction temperature 180 ~ 300 ℃.

[0042] After testing, the toluene removal rate can reach 90% at 232℃, and the toluene catalytic effect is Figure 2 Example 1 in .

[0043] Example 2

[0044] The method for preparing a copper-manganese spinel nanomaterial with a high oxygen vacancy content in this embodiment comprises the following steps:

[0045] S1. Take 0.02 mol Cu(NO3)2·3H2O and 0.04 mol Mn(NO3)2·5H2O in 20 mL of deionized water and stir at 60°C for 30 min; then add 0.3 g of waste activated carbon powder and continue stirring for 2 h to make the carbon material evenly distributed in the solution to obtain a carbon material that adsorbs metal ions.

[0046] S2. Add 20 mL of 5 mol / L NaOH solution to the solution obtained in S1 to precipitate all metals in the solution. Filter the obtained precipitate and wash it 4 times until the filtrate is neutral.

[0047] S3. Dry the separated precipitated product in an oven at 95° C. for 12 h, and then transfer it to a muffle furnace at 500° C. and calcine it for 3 h to obtain a copper-manganese spinel catalyst with a high oxygen vacancy content.

[0048] See also Figure 1 When 0.3 g of waste activated carbon was added, CuMn2O4 spinel was successfully synthesized. The N2 adsorption isotherm of the obtained sample is shown in Figure 3 It can be seen that it conforms to the IV type adsorption isotherm, and the characteristics are the same as those in Example 1. Figure 4 From the energy distribution surface scanning analysis photo in (a), it can be observed that copper and manganese are evenly distributed without obvious agglomeration.

[0049] In order to verify the VOCs catalytic oxidation performance of the obtained copper-manganese spinel catalyst with high oxygen vacancy content, a toluene catalytic performance test was performed on it, including the following steps:

[0050] 100 mg of the prepared copper-manganese spinel catalyst with high oxygen vacancy content was loaded into a fixed-bed quartz tube reactor, and a VOCs catalytic oxidation degradation experiment was carried out under air atmosphere, wherein the background concentration of toluene was 300 ppm, the total flow rate was 100 ml / min, and the space velocity was 60000 mL·h -1 ·g -1 , reaction temperature 180 ~ 300 ℃.

[0051] After testing, the toluene removal rate can reach 90% at 212℃, and the toluene catalytic effect is Figure 2 Example 2 in .

[0052] Example 3

[0053] The method for preparing a copper-manganese spinel nanomaterial with a high oxygen vacancy content (i.e., a high oxygen defect content) of the present embodiment specifically comprises the following steps:

[0054] S1. Take 0.02 mol Cu(NO3)2·3H2O and 0.04 mol Mn(NO3)2·5H2O in 20 mL of deionized water and stir at 60°C for 30 min; then add 0.5 g of waste activated carbon powder and continue stirring for 2 h to make the carbon material evenly distributed in the solution to obtain a carbon material solution that adsorbs metal ions.

[0055] S2. Add 20 mL of 5 mol / L NaOH solution to the solution obtained in S1 to precipitate all metals in the solution. Filter the obtained precipitate and wash it 4 times until the filtrate is neutral.

[0056] S3. Dry the separated precipitated product in an oven at 95° C. for 12 h, and then transfer it to a muffle furnace at 500° C. and calcine it for 3 h to obtain a copper-manganese spinel catalyst with a high oxygen vacancy content.

[0057] See also Figure 1 , CuMn2O4 spinel was successfully synthesized when 0.5 g of spent activated carbon was added.

[0058] In order to verify the VOCs catalytic oxidation performance of the obtained copper-manganese spinel catalyst with high oxygen vacancy content, a toluene catalytic performance test was performed on it, including the following steps:

[0059] 100 mg of the prepared copper-manganese spinel catalyst with high oxygen vacancy content was loaded into a fixed-bed quartz tube reactor, and a VOCs catalytic oxidation degradation experiment was carried out under air atmosphere, wherein the background concentration of toluene was 300 ppm, the total flow rate was 100 ml / min, and the space velocity was 60000 mL·h -1 ·g -1 , reaction temperature 180 ~ 300 ℃.

[0060] After testing, the toluene removal rate can reach more than 90% at 218℃, and the toluene catalytic effect is Figure 2 Example 3 in .

[0061] Example 4

[0062] The method for preparing a copper-manganese spinel nanomaterial with a high oxygen vacancy content in this embodiment comprises the following steps:

[0063] S1. Take 0.02 mol Cu(NO3)2·3H2O and 0.04 mol Mn(NO3)2·5H2O in 20 mL of deionized water and stir at 60°C for 30 min; then add 0.7 g of waste activated carbon powder and continue stirring for 2 h to make the carbon material evenly distributed in the solution to obtain a carbon material that adsorbs metal ions.

[0064] S2. Add 20 mL of 5 mol / L NaOH solution to the solution obtained in S1 to precipitate all metals in the solution. Filter the obtained precipitate and wash it 4 times until the filtrate is neutral.

[0065] S3. Dry the separated precipitated product in an oven at 95° C. for 12 h, and then transfer it to a muffle furnace at 500° C. and calcine it for 3 h to obtain a copper-manganese spinel catalyst with a high oxygen vacancy content.

[0066] The N2 adsorption isotherm of the copper-manganese spinel catalyst with high oxygen vacancy content obtained in this example is shown in FIG. Figure 3 It can be seen that it conforms to the type IV adsorption isotherm, and the characteristics are the same as those in Example 1.

[0067] See also Figure 1 When 0.7 g of waste activated carbon was added, CuMn2O4 spinel was successfully synthesized. The N2 adsorption isotherm of the obtained sample is shown in Figure 3It can be seen that it conforms to the type IV adsorption isotherm, and the characteristics are the same as those in Example 1.

[0068] In order to verify the VOCs catalytic oxidation performance of the obtained copper-manganese spinel catalyst with high oxygen vacancy content, a toluene catalytic performance test was performed on it, including the following steps:

[0069] 100 mg of the prepared copper-manganese spinel catalyst with high oxygen vacancy content was loaded into a fixed-bed quartz tube reactor, and a VOCs catalytic oxidation degradation experiment was carried out under air atmosphere, wherein the background concentration of toluene was 300 ppm, the total flow rate was 100 ml / min, and the space velocity was 60000 mL·h -1 ·g -1 , reaction temperature 180 ~ 300 ℃.

[0070] After testing, the toluene removal rate can reach 90% at 224℃, and the toluene catalytic effect is Figure 2 Example 4 in .

[0071] Comparative Example 1

[0072] The preparation method of a copper-manganese spinel nanomaterial with a high oxygen vacancy content in this comparative example specifically comprises the following steps:

[0073] S1. Take 0.02 mol Cu(NO3)2·3H2O and 0.04 mol Mn(NO3)2·5H2O in 20 mL of deionized water and stir at 60°C for 30 min.

[0074] S2. Add 20 mL of 5 mol / L NaOH solution to the solution obtained in S1 to precipitate all metals in the solution. Filter the obtained precipitate and wash it 4 times until the filtrate is neutral.

[0075] S3. Dry the separated precipitated product in an oven at 95° C. for 12 h, and then transfer it to a muffle furnace at 500° C. and calcine it for 3 h to obtain a copper-manganese spinel catalyst with a high oxygen vacancy content.

[0076] It can be seen from the above steps that, compared with Examples 1 to 4, this comparative example does not add waste activated carbon in step S1.

[0077] See also Figure 1 , Comparative Example 1 also successfully synthesized CuMn2O4 spinel. The N2 adsorption isotherm of the obtained sample is shown in Figure 3 It can be seen that it conforms to the type IV adsorption isotherm, and the characteristics are the same as those in Example 1.

[0078] In order to verify the VOCs catalytic oxidation performance of the obtained copper-manganese spinel catalyst with high oxygen vacancy content, a toluene catalytic performance test was performed on it, including the following steps:

[0079] 100 mg of the prepared copper-manganese spinel catalyst with high oxygen vacancy content was loaded into a fixed-bed quartz tube reactor, and a VOCs catalytic oxidation degradation experiment was carried out under air atmosphere, wherein the background concentration of toluene was 300 ppm, the total flow rate was 100 ml / min, and the space velocity was 60000 mL·h -1 ·g -1 , reaction temperature 180 ~ 300 ℃.

[0080] After testing, the toluene removal rate reached 90% at 256℃, and the toluene catalytic effect was Figure 2 Comparative Example 1 in .

[0081] See also Figure 4 , Figure 4 (a) and (b) are the EDS element distribution spectra of the catalysts prepared in Example 2 and Comparative Example 1, respectively. It can be seen from the figures that there is no obvious difference in the element distribution of the catalysts in Example 2 and Comparative Example 1, which indicates that the addition of waste activated carbon material has no obvious effect on the elements and structure of the spinel material.

[0082] See also Figure 5 , which are EPR graphs of the catalysts obtained in Example 2 and Comparative Example 1, are used to characterize the oxygen vacancy content of the spinel, wherein the peak intensity reflects the relative content of oxygen vacancies. It can be seen from the figure that due to the addition of waste activated carbon in the scheme of Example 2, a large amount of oxygen is consumed by the carbon during calcination, thereby obtaining a large amount of oxygen vacancies. The present application successfully synthesized a spinel material with rich oxygen vacancy content through the use of waste activated carbon and simple operating steps. And the oxygen vacancies of the material can be regulated without other complicated and tedious treatments, thereby affecting its catalytic performance. According to Figure 2 It can be seen that by adding waste activated carbon, the toluene removal rate increases in the temperature range of 180 to 300°C under the same test conditions, indicating that the performance of the catalyst prepared after adding waste activated carbon is better.

[0083] As a specific implementation method, the process of obtaining the waste activated carbon powder used in each embodiment of the present application is as follows: under normal production conditions of a chemical enterprise, commercial activated carbon is used to adsorb and purify the production exhaust gas, that is, to adsorb substances such as VOCs, and the adsorption time is 90 to 180 days to obtain waste activated carbon, which is then ground into 60-mesh powder.

[0084] Those skilled in the art can understand that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions recorded in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a copper-manganese spinel nanomaterial with a high oxygen vacancy content, characterized in that: The preparation method comprises the following steps: Dissolve the metal salt in deionized water, stir evenly, then add the waste activated carbon powder, stir thoroughly to obtain a uniformly dispersed mixed solution; Adding an excess amount of the alkaline solution to the mixed solution to fully precipitate the metal, and after the reaction is completed, filtering and washing the reaction precipitate until the filtrate is neutral, and separating and obtaining a precipitated product; The precipitated product is dried and then transferred to a muffle furnace for calcination to obtain a copper-manganese spinel catalytic material with a high oxygen vacancy content; The metal salts include copper salts and manganese salts.

2. The preparation method according to claim 1, characterized in that: The molar ratio of the waste activated carbon to the metal salt is 0.14 to 1; The molar ratio of the copper salt to the manganese salt is 1:1.25 to 1:2.5, and the total concentration of the copper salt and the manganese salt in the mixed solution is 2 to 3 mol / L.

3. The preparation method according to claim 1, characterized in that: The calcination treatment is performed at 400-600° C. for 2-5 hours.

4. The preparation method according to claim 1, characterized in that: The drying process is carried out at 95 to 120° C. for 12 to 24 hours.

5. The preparation method according to claim 1, characterized in that: The molar ratio of the alkaline solution to the metal salt is 1:2.4 to 1:

3.

6. The preparation method according to claim 1, characterized in that: The copper salt includes one or more of copper nitrate, copper sulfate, copper chloride, and organic copper salts; the manganese salt includes one or more of manganese nitrate, manganese sulfate, manganese chloride, and organic manganese salts.

7. The preparation method according to claim 1, characterized in that: The alkaline solution is sodium hydroxide, potassium hydroxide, or ammonia solution; the concentration of the alkaline solution is 4-8 mol / L.

8. The preparation method according to claim 1, characterized in that: After the metal salt is dissolved in deionized water, the stirring time is 30 to 60 minutes; after the waste activated carbon powder is added, the sufficient stirring time is 60 to 240 minutes; after the excess alkaline solution is added to the mixed solution, the mixture is sufficiently and rapidly stirred for 40 to 80 minutes to fully precipitate the metal.

9. The preparation method according to claim 1, characterized in that: The waste activated carbon is waste activated carbon generated in the process of treating industrial waste gas, waste water or indoor polluted gas.

10. An application, wherein the copper-manganese spinel catalytic material with a high oxygen vacancy content obtained by the preparation method according to any one of claims 1 to 9 is applied to catalytic oxidation degradation of VOCs.